2007
DOI: 10.1017/s0007114507871686
|View full text |Cite
|
Sign up to set email alerts
|

Diet restriction and ageing in the dog: major observations over two decades

Abstract: This report reviews decade two of the lifetime diet restriction study of the dog. Labrador retrievers (n 48) were paired at age 6 weeks by sex and weight within each of seven litters, and assigned randomly within the pair to control-feeding (CF) or 25 % diet restriction (DR). Feeding began at age 8 weeks. The same diet was fed to all dogs; only the quantity differed. Major lifetime observations included 1·8 years longer median lifespan among diet-restricted dogs, with delayed onset of late life diseases, espec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
106
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(131 citation statements)
references
References 80 publications
11
106
0
2
Order By: Relevance
“…Diet quality has been shown to have a mixed impact on the survivorship of other crustaceans, such as amphipods, whose survivorship on diets that mix high-and low-quality food sources varies widely depending on the species (Cruz-Rivera & Hay 2000a,b), and diet quantity is inversely correlated with longevity in a variety of species (e.g. Lawler et al 2008, Pietrzak et al 2010. Alternatively, the inclusion of nitrogen-rich animal tissue in its diet significantly improved the reproductive investment and physiological condition of Aratus pisonii.…”
Section: Discussionmentioning
confidence: 99%
“…Diet quality has been shown to have a mixed impact on the survivorship of other crustaceans, such as amphipods, whose survivorship on diets that mix high-and low-quality food sources varies widely depending on the species (Cruz-Rivera & Hay 2000a,b), and diet quantity is inversely correlated with longevity in a variety of species (e.g. Lawler et al 2008, Pietrzak et al 2010. Alternatively, the inclusion of nitrogen-rich animal tissue in its diet significantly improved the reproductive investment and physiological condition of Aratus pisonii.…”
Section: Discussionmentioning
confidence: 99%
“…Design strategies that may help to reduce or address the associated biases include: starting follow-up at younger ages before obesity and most diseases have begun, use of the g-computation algorithm and related approaches, 38,43,44 sensitivity analyses and simulations. 42 Use of additional evidence such as experimental results, use of intermediate outcomes and biomarkers, 45 animal studies, [46][47][48] as well as other considerations described by Bradford Hill 49 should, of course, help the researcher to evaluate the magnitude of effects, although considerable uncertainty may remain.…”
Section: Discussionmentioning
confidence: 99%
“…12 Research has indicated that in laboratory animals, pigs and dogs 25 a restrictive diet increases lifespan and delays onset of species-specific degenerative diseases especially osteoarthritis in dogs. However, negative welfare states such as increased hunger, stress elevation, behavioural changes (increased aggression & stereotypies) may occur with food restriction.…”
Section: Animal Welfarementioning
confidence: 99%